Prevalence and Related Factors of Anxiety Among University Teachers 1 Year After the COVID-19 Pandemic Outbreak in China: A Multicenter Study - Fu, Wenning; Han, Xiaotong; Liu, Yifang; Zou, Li; Wen, Jing; Yan, Shijiao; Lv, Chuanzhu (Frontiers in Psychiatry, 2022)
Objectives This study aimed to evaluate the prevalence of anxiety among university teachers 1 year after the onset of the coronavirus disease 2019 (COVID-19) pandemic and provide empirical evidence of psychological intervention. Methods A multicenter study was conducted to examine the prevalence of anxiety among 10,302 teachers in 21 Chinese universities from February 12 to April 23, 2021. The generalized Anxiety Disorder 7-item Scale (GAD-7) was used to assess symptoms of anxiety. Multivariate logistic regression models were used to analyze the relationship between potential influence and anxiety symptoms. Results The overall prevalence of anxiety was 40.0% 1 year after the onset of the COVID-19 pandemic, which was found to be higher in women than in men (41.32% vs. 38.22%; p < 0.0001). The multivariate logistic regression showed that being the female (OR = 1.207; 95%CI: 1.103–1.318), age ≥60 years (OR = 2.004; 95%CI: 1.128–3.560), being married (OR = 1.319; 95%CI: 1.150–1.513), and poor family economic status (OR = 1.580; 95%CI: 1.321–1.891) were significantly associated with anxiety. Participants with moderate, slight, or no impact of COVID-19 on life (OR for moderate, 0.557; 95%CI, 0.508–0.611; OR for slight/no, 0.377; 95%CI, 0.323–0.439) showed a reduced risk of anxiety compared to those who reported a significant effect. Conclusions Symptoms of anxiety were found in about two-fifths of Chinese university teachers 1 year after the outbreak of the COVID-19 pandemic. Our findings suggest that the government should improve the dynamic tracking of mental health and adopt long-term intervention strategies.